Relationships between fish size and otolith size of four bathydemersal fish species from the south eastern Arabian Sea, India. (February 2017) - Aneesh Kumar, K. V.; Deepa, K. P.; Hashim, M.; Vasu, C.; Sudhakar, M.
Summary: The objective of this study was to estimate a prey body size from the hard parts (e.g. otoliths) of a fish species frequently found in the guts of predators. Length–weight relationships between otolith size (length, height, weight and aspect ratio) and fish size (total length and weight) were determined for four fish species captured in the Arabian Sea by bottom trawl (2015 survey on‐board FORV Sagar Sampada, 200–300 m depth), off the west coast of India: Psenopsis cyanea, Pterygotrigla hemisticta, Bembrops caudimacula and Hoplostethus rubellopterus . No significant differences were noted between the size of the left and right otoliths ( t test) in any of the four species. The length–weight relationship of the otolith in all four species showed a negative allometric growth pattern ( t test, p < .05). The data fitted well to the regression model for otolith length (OL), otolith height (OH) and otolith weight (OW) to total length (TL) and total weight (TW). Results showed that these relationships are a helpful tool in predicting fish size from the otoliths and in calculating the biomass of these less‐studied fish species during feeding studies and palaentology.